Everything you need to know about genetically modified foods - Freedman, Jeri (New York : The Rosen, 2002)
Details recent developments pertaining to genetic modification of food, including where the research is taking place and how it affects agriculture and the consumer.
Includes bibliographical references and index.
Keywords: Genetically modified foods -- Juvenile literature